(untitled) (Vietnam Journal of Community Medicine, 2026)
Research objective: To analyze certain psychosocial factors associated with generalized anxiety disorder (GAD) in patients with psoriasis. Subjects and methods: A cross-sectional descriptive study was conducted on 236 patients diagnosed with psoriasis vulgaris who were examined and treated at the National Hospital of Dermatology and Venereology during 2025–2026. Results: Being single was associated with GAD (OR = 2.88; 95% CI: 1.02–8.10; p = 0.049), and perceived stigma was associated with GAD (OR = 6.49; 95% CI: 2.99–14.05; p < 0.001). No statistically significant associations were found regarding age, age of psoriasis onset, or disease duration. Conclusion: GAD is an issue requiring attention in patients with psoriasis. Perceived stigma is a factor associated with GAD, suggesting a need to integrate the screening and detection of GAD symptoms, the assessment of stigma experiences, and the provision of psychosocial support and supportive resources into the management of psoriasis patients.